Influence of Internal and External factors on Supply Chain Information System Risk Management Implementation - Yang-Ngam, Chaleeya; Chankoson, Thitinan; Aodton, Pornpimon (International Journal of Supply Chain Management, 2019)
Risk management is major part of every enterprise. Proper risk management in all the department of an organization is one of the guaranties of success. However, Indonesian supply chain companies are lacking in information system (IS) risk management implementation. These companies are facing internal and external issues due to which the performance of Indonesian supply chain companies is not up to the mark. Thus, the objective of this study is to examine the role of internal and external factors in supply chain IS risk management implementation. Thus, the data is collected by collaborating with supply chain employees in Indonesia. Accordingly, primary data is used in this study to approach end results. Results of the study highlighted that various internal and external factors have important relationship with supply chain IS risk management implementation. Internal factor namely; organization culture and management commitment have positive effect on IS risk management implementation. External factor, namely; competitive pressure also has important role. Additionally, organization structure is one of the factors which strengthen the positive relationship of management commitment and supply chain IS risk management implementation.